EKSISTENSI PERAN AYAH DALAM MENYIAPKAN GENERASI MUSLIM YANG SHALEH - Nur Hayani Hayani (Jurnal Al-Fatih, 2020)
Fathers as men have personalities that are generally different from women. The father figure cannot be replaced by the mother. Regardless of whatever mother, he cannot replace the position of a man called a father. Being a good father is one of the normal ideals of a man who has a family. As a good father, father's involvement in a child's life is an absolute necessity. Fathers who are involved and sensitive in childcare will have a positive effect. Her role in the family, interactions with mothers, children and the community will be a model for children in the learning process at every stage of their lives. Father's behavior affect deeply and has positive values ​​that will stay in a child's heart. Similarly, the negative influence will be very easy to decrease to their children. A father figure is needed by a child, in the presence of his children, a father is a determinant stock of piety for children.